Economic and welfare implications of the reduction of US foreign assistance in Malawi - Cockx, Lara; De Weerdt, Joachim; Duchoslav, Jan; Jamali, Andrew; Nagoli, Joseph; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2025)
For over a decade, the US has consistently ranked as either the largest or second-largest donor to Malawi. Annual foreign assistance disbursements have averaged over $360 million between 2020 and 2023. In January 2025 the US government suspended all US-funded foreign aid programs. As of April 2025, the available information suggests that funding for many of these programs in Malawi has been withdrawn, resulting in an estimated decline in US foreign assistance to Malawi of around 59% for 2025. As a result, Malawi faces a potential decline in foreign exchange inflows of around $177 million in 2025, a loss equivalent to approximately 6.3% of the annual merchandise import bill. With Malawi’s economy currently highly vulnerable, lacking the buffers needed to absorb shocks, the eco nomic and welfare implications of these recent events are concerning. The suspensions may lead to an economic contraction from reduced activities by US implementing partners, immediate pressure on the exchange rate (endangering the affordability or availability of critical imports) and declining productivity in key sectors such as agriculture. Deteriorating health and education outcomes could further affect the productivity of workers in the longer run. In this policy note we combine qualitative and quantitative information gathered in-country with modeled results of the possible economywide impacts of the reduction of US foreign assistance on key economic and welfare indicators over the next six years. We also discuss policy options that could help mitigate some of the adverse impacts.